197 Awardee Talk: Novel Management Strategies to Enhance Growth and Development of Feedlot Receiving Cattle. (8th October 2021) - Cooke, Reinaldo F
Abstract: Feedlot receiving is one of the most critical phases within the beef production cycle, when cattle are exposed to several stress and health challenges that impact their welfare and productivity. These stressors include weaning, road transport, and commingling with different animals, which elicit adrenocortical and acute-phase protein responses known to impair cattle immunocompetence and growth. Accordingly, incidence of bovine respiratory disease (BRD) is elevated during feedlot receiving, despite efforts to minimize stress and vaccination protocols against BRD pathogens. With increased restrictions regarding the use of feed-grade antimicrobials in livestock systems, our research group has focused on developing management systems that minimize stress and enhance performance and immunity of receiving cattle. By providing all vaccines against BRD pathogens prior to feedlot entry, our group reported increased (P ≤ 0.05) vaccine efficacy, body weight (BW) gain, feed efficiency, and reduced BRD incidence during the receiving period compared to on-arrival or delayed vaccination. Reducing the number of cattle sources within receiving pens, as a manner to alleviate commingling stress, reduced (P = 0.04) the number of antimicrobials needed for cattle diagnosed with BRD to regain health. Administration of a bovine appeasing substance (BAS) to beef cattle at weaning alleviated (P ≤ 0.05) the resultant acute-phase protein response, enhanced humoral immunity against BRD pathogens, and improved BW gain during a 6-wk postweaning period. Likewise, BAS administration to steers upon feedlot arrival facilitated (P ≤ 0.05) early detection of BRD signs and lessened the BRD recurrence upon first antimicrobial treatment, resulting in improved (P ≤ 0.05) BW gain and feed efficiency during a 45-d receiving period. Collective, vaccinating cattle against BRD prior to feedlot arrival, reducing the number of cattle sources within receiving pens, and the use of BAS during stressful events are favorable strategies to enhance performance and immunity of feedlot cattle.